2015
DOI: 10.1016/j.biopsych.2014.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Scalp Hair Follicles as a Novel Source of Biomarker Genes for Psychiatric Illnesses

Abstract: Scalp hair follicles could be a beneficial genetic biomarker resource for brain diseases, and further studies of FABP4 are merited in schizophrenia pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Maekawa et al utilized scalp hair follicles as a source of biomarker genes and found that the gene CNTNAP2 showed significantly decreased expression in samples from subjects with ASD compared with control follicles (Maekawa et al, 2015). …”
Section: Hair Follicle Gene Expression Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maekawa et al utilized scalp hair follicles as a source of biomarker genes and found that the gene CNTNAP2 showed significantly decreased expression in samples from subjects with ASD compared with control follicles (Maekawa et al, 2015). …”
Section: Hair Follicle Gene Expression Studiesmentioning
confidence: 99%
“…CNTNAP2, a neurexin family protein that acts as a neuronal adhesion molecule and receptor. It was found to be a direct neural target of the human FOXP2 protein, and mutations of FOXP2 and CNTNAP2 were linked to language and speech disorders in ASD (Maekawa et al, 2015). The FOXP1 gene, which was found to be elevated in ASD subjects according to Chien et al functions as a transcription repressor, forms a heterodimer with FOXP2, and is co-expressed with FOXP2 in numerous brain regions, suggesting close functional cooperation between the two proteins.…”
Section: Gene Expression In Asd-summary (Table 2)mentioning
confidence: 99%
“…Plucked follicles are also amenable to image analysis in order to quantify treatment-related changes of specific markers. For example, a trend toward downregulation of fatty acid binding protein 4(FABP4) expression in plucked human scalp hair follicles was found to be correlated with a diagnosis of schizophrenia, suggesting that the use of plucked hair follicles could be a beneficial genetic biomarker resource for brain diseases (Maekawa et al 2015).…”
Section: Plucked Human Scalp Hair Follicle Analysismentioning
confidence: 99%
“…; Maekawa et al. ), hair follicles were used to explore the HIIT‐responsive transcriptomic biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…; Maekawa et al. ). It has also been suggested as a potential minimally‐invasive model to study global changes in gene expression with various modes of physical activity (Takahashi et al.…”
Section: Introductionmentioning
confidence: 97%